Cover Feature: Stereoselective Thioconjugation by Photoinduced Thiol‐ene Coupling Reactions of Hexo‐ and Pentopyranosyl d‐ and l‐Glycals at Low‐Temperature—Reactivity and Stereoselectivity Study (Chem. Eur. J. 64/2019). Issue 64 (8th October 2019) - Kelemen, Viktor; Bege, Miklós; Eszenyi, Dániel; Debreczeni, Nóra; Bényei, Attila; Stürzer, Tobias; Herczegh, Pál; Borbás, Anikó
Abstract : Radical‐mediated hydrothiolation of enoses was studied as a stereoselective method for synthesizing challenging oligosaccharide structures. Three types of glycals were reacted with various thiols using UV irradiation at the temperature range of rt to −120 °C, producing 39 thioglycosides up to tetrasaccharide. Cooling always proved to be beneficial to the efficacy, −80 °C being the optimal temperature in most cases. The different conformational preferences of the intermediate carbon‐centered radicals were crucial in the stereoselectivity of the reactions. More information can be found in the Full Paper by A. Borbás et al. on page 14555 .